2003
DOI: 10.1023/a:1022630924236
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Retention of the second polar body and chromosome malsegregation were observed after parthenogenetic activation, either spontaneous or induced by puromycin. This means that using parthenogenetic embryos for stem cell research will require great care and attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Eventually, some oocytes differentiate into parthenotes with a trophectoderm (te, Figure  12D and E), blastocoele (bc) and inner cell mass (icm) [179], similarly to some oocytes in in vitro fertilization (IVF) cultures [186]. This indicates that the OSC-derived oocytes developed in vitro are functionally similar to the mature follicular oocytes.…”
Section: Developmental Potential Of Ovarian Stem Cells In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, some oocytes differentiate into parthenotes with a trophectoderm (te, Figure  12D and E), blastocoele (bc) and inner cell mass (icm) [179], similarly to some oocytes in in vitro fertilization (IVF) cultures [186]. This indicates that the OSC-derived oocytes developed in vitro are functionally similar to the mature follicular oocytes.…”
Section: Developmental Potential Of Ovarian Stem Cells In Vitromentioning
confidence: 99%
“…Some of these OSC-derived epithelial cells appear to be precursors of gradually differentiating oocytes. Spontaneous development of parthenogenetic embryos in ovarian cultures, which can also be observed during oocyte handling for standard IVF purposes [186], indicates the functional similarity of in vitro developed eggs with cultured follicular oocytes. Development of oocytes from OSC derived from ovaries with no naturally present follicles and oocytes (POF and postmenopausal women) [94,189] confirms the ability of OSC to produce new eggs in the absence of OSC niche present during neo-oogenesis in vivo .…”
Section: Developmental Potential Of Ovarian Stem Cells In Vitromentioning
confidence: 99%
“…Recent studies reported that human unfertilized eggs undergo parthenogenetic activation in vivo and in vitro (1213). This may contribute germ cell derived ovarian teratomas in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Among all factors, exposure to cold and prolonged retention in the oviduct after animal sacrifice can significantly increase rat OSA ( Keefer and Schuetz, 1982 ; Zernicka-Goetz, 1991 ; Kito et al, 2010 ). Another widely recognized factor is postovulatory aging, which has been shown in rat ( Ben-Yosef et al, 1995 ; Chaube et al, 2007 ; Cui et al, 2012 ), golden hamster ( Sun et al, 2002 ; Jiang et al, 2015 ), and human ( Santos et al, 2003 ) to facilitate OSA ( Table 1 ). Same as other vertebrates, the two most critical kinases of cytostatic factor (CSF), maturation-promoting factor (MPF), and mitogen-activated protein kinase (MAPK), are also involved in OSA ( Tiwari et al, 2018 ).…”
Section: Mechanism and Control Of Type-1 Osamentioning
confidence: 99%